Self-healing hydrogels with stimuli responsiveness based on acylhydrazone bonds. (3rd January 2019) - Sun, Chengyuan; Jia, Haiyan; Lei, Kun; Zhu, Dandan; Gao, Yahan; Zheng, Zhen; Wang, Xinling
Abstract: Thermo-responsive hydrogels consist of natural and synthetic macromolecules were presented based on dynamic acylhydrazone formation, which is self-healable and pH-sensitive. Hydrazone groups modified poly(N-isopropylacrylamide) (PNIPAM) copolymers and aldehyde groups exposed oxidized sodium alginate (OSA) were adopted to prepare the functional hydrogels without any catalyst. Specifically, acylhydrazone bonds, which were served as cross-linking points, endowed the hydrogels with self-healing property confirmed by rheological recovery test. Meanwhile, the hydrogels displayed obvious reversible sol-gel transition under different conditions, leading to that the hydrogels were able to be reshaped repeatedly exposed to pH trigger. Besides, due to the PNIPAM segments were served as the frameworks, the hydrogels were testified to exhibit tunable phase transition temperature between 30 °C and 40 °C around body temperature, which was regulated by variation in aldehyde and hydrazone ratio. The as-prepared hydrogels with self-healing and dual stimuli-responsive properties are beneficial to their bioapplications as drug delivery system, biosensors and soft tissue filling agents, etc. Graphical abstract: Highlights: Natural and synthetic macromolecules were adopted to prepare the hydrogels. Self-healing property was presented based on acylhydrazone bonds. The hydrogels exhibit both pH and thermo dual response. The hydrogels are able to be reshaped repeatedly exposed to pH trigger. Tunable phase transition temperature was regulated around body temperature.